2021
DOI: 10.21203/rs.3.rs-633983/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Baihu and Guizhi Decoction in acute gouty arthritis: a randomized, double-blind, controlled clinical study

Abstract: Background The prevalence rates of gout worldwide have increased annually. Acute gouty arthritis (AGA) accounts for a large proportion of gout patients and causes severe physical and mental pain in patients. Controlling the occurrence and development of gout inflammation is the first step in the treatment of gout. The main treatment drugs in gout are Non-Steroid Anti-Inflammatory Drugs (NSAIDS), colchicine and glucocorticoids, but these treatments have many adverse reactions which limit their clinical applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Fourteen studies reported the score of VAS. [36,38,46,48,49,52,53,57,76,77,83,92,109,111] There were 626 patients in the treatment group and 620 in the control group. Meta-analysis indicated that TCMD treatment had a better effect on reducing the score of VAS than routine treatment (I 2 = 96.39%, random effects model, WMD = −0.98, 95% CI [−1.66, −0.30], P < .001, Fig.…”
Section: Visual Analogue Scale (Vas)mentioning
confidence: 99%
See 4 more Smart Citations
“…Fourteen studies reported the score of VAS. [36,38,46,48,49,52,53,57,76,77,83,92,109,111] There were 626 patients in the treatment group and 620 in the control group. Meta-analysis indicated that TCMD treatment had a better effect on reducing the score of VAS than routine treatment (I 2 = 96.39%, random effects model, WMD = −0.98, 95% CI [−1.66, −0.30], P < .001, Fig.…”
Section: Visual Analogue Scale (Vas)mentioning
confidence: 99%
“…All studies mentioned randomization and 49 studies described the method of randomization as a random number table. [18,20,23,24,[41][42][43]46,[48][49][50]52,53,55,[58][59][60][61]63,64,[66][67][68]70,72,74,75,[78][79][80][84][85][86][88][89][90][94][95][96][98][99][100][101]104,106,107,109,111] Therefore, in terms of selection bias, the 49 studies were rated as low risk, and the rest were rated as unclear risk or high risk. Overall, the quality of included studies was not high.…”
Section: Bias Assessmentmentioning
confidence: 99%
See 3 more Smart Citations